Muhammad Abduh and the Conception of Science: The Framework of Maqasid and Sharia - Ahmad Nabil Amir; Tasnim Abdul Rahman; Seyed Mohammad Houshisadat; Musa Adebayo Badrudeen (al-Battar: Jurnal Pamungkas Hukum, 2025)
This research uses a qualitative method with a library research approach and biographical analysis. Data were collected from Abduh's major theological and scientific works, such as Al-Islām wa al-Naṣrāniyyah ma'a al-'Ilm wa al-Madaniyyah, Tafsīr al-Manār, Tafsīr Juz 'Amma, and Risālat al-Tawḥīd, and supported by relevant secondary literature. The analysis was carried out by examining the main themes related to rational thought, the integration of science and religion, and Abduh's contribution to Islamic modernity. The results of the study show that Abduh made an important contribution in developing a scientific approach to religious texts, especially through the interpretation of the Qur'an which emphasizes the superiority of reason ('aql), freedom of thought (taḥarrur), and rationality. His views not only integrated modern science with Islamic values, but also encouraged the revival of intellectual consciousness and the formation of a dynamic Islamic worldview (weltanschauung). In conclusion, Muhammad Abduh's scientific thought became an important foundation for the renewal of modern Islam. His ideas not only strengthened the rational approach to understanding religious texts, but also provided a new direction for the development of Islamic civilization that was able to dialogue with the progress of science and technology without losing the essence of its spirituality.